Intermedial Performance and the vertical perspective - Christoffersen, Erik Exe (Peripeti, 2017)
Why Does Night Come Mother can be considered as a focus change or paradigm shift in relation to intermedial performing arts. The performance re-inscribes reality in the participatory process that takes place in the body of the consciousness of the spectator. At the same time the performance is a staged construction with an audience taking part. The performance destabilizes the balance of the spectator’s sense of vision.